Representation of Women’s Beauty in Kosé Sekkisei White UV Emulsion - R. Ramdani; M. Ali (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The beauty of women has always been a separate conversation in society. Women’s beauty is very diverse, but generally beautiful is always synonymous with white skin and this idea is often targeted at audiences in advertising, especially Japan. Advertisements so far have shown beauty through physical appearance that emphasizes certain characteristics of beauty as a female attraction. The beauty shown or used in advertisements is generally based on a background of beauty myths that developed in Japan, one of which is white skin. In the midst of the existence of these advertisements, Kose advertisements then appear to participate in promoting these beauty ideas or myths. This study seeks to determine the representation of female beauty in Kose advertisements by looking at Japanese women’s beauty myths. The research method chosen is qualitative. The beauty of Japanese women is an interesting thing to study regarding one’s views on women’s beauty myths according to society and advertisements. This study uses semiotic theory, representation theory and beauty myths. Through the semiotic method it was found that Kose advertisements represented the white and shining beauty of Japanese women. In conclusion, white skin remains a criterion in Japanese beauty and this indicates that the Kose advertisement is still related to the Japanese beauty myth which states that white skin is beautiful